Advances in nanoparticle development for improved therapeutics delivery: nanoscale topographical aspect. (September 2019) - Singh, Rajendra K; Knowles, Jonathan C; Kim, Hae-Won
Nanoparticle-based therapeutics delivery holds great promise for the treatment of intractable diseases. The high loading of drug molecules and their precise delivery to target sites are needed to gain optimal therapeutic functions of the nanoparticle delivery system. In this communication, we highlight, among other properties of nanoparticles (e.g. size, shape, surface chemistry, and degradation), the nanoscale topography, which has recently been shown to be an important parameter, ultimately determining drug loading, cell penetration, and body clearance. This nanotopographical aspect is considered to offer a new effective strategy to the development of nanoparticles for drug and gene delivery with enhanced therapeutic outcome.